EFFECT OF RASA MEZHUGU ON FREUND’S ADJUVANT-INDUCED ARTHRITIS IN RATS - Nandhagopal, K.; Kanniyakumari, M. (International Journal of Current Pharmaceutical Research, 2016)
Objective: Rheumatoid arthritis is a long-lastingÂ autoimmune disorderÂ that primarily affectsÂ joints. It typically results in warm, swollen, andÂ painfulÂ joints. Pain and stiffness often worsen the following rest. The goal of treatment is to reduce pain, decrease inflammation, and improve a person’s overall functioning. In spite of tremendous development in the field of synthetic drugs during recent years, the side effects could not be avoided. Hence the current research focus is to develop less toxic drugs as early as feasible in the disease process. Methods: A 90 d old Wistar male rat was used for the research and was divided into four groups treated with Saline, Palm Jaggary, Rasa Mezhugu and Indomethacin. Results: Acute toxicity study, Sub Acute study, Anti-arthritic study and histological findings showed that the Rasa Mezhugu has an anti-arthritis effect. Conclusion: Further the histopathology slide photos of bone, cerebrum, cardiac muscle, kidney, liver, pancreas, ovaries, lungs, testes, stomach and spleen proved the safety of Rasa Mezhugu in rats.